KETERAMPILAN KOMUNIKASI MATEMATIS SISWA PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI SELF EFFICACY - Melawati, Nur Asri; Nurdin, Erdawati (Math Educa Journal, 2021)
Mathematical communication skills are one of the competencies that students must have in the 21st century.  This study aims to anylize and describe students’ mathematical communication skills in terms of self efficacy on the polyhedrons material. The research used descriptive qualitative methods. The subjects were 9 grade students of An nashichah private junior high school selected purposively.  Data was collected through online test, questionnaires and interviews using WhatsApp. The data analyzed through 3 stages, namely data reduction, data presentation and conclusions. The results showed that the students’ mathematical communication skills were low. When viewed from students’ self efficacy, high self efficacy students have high mathematical communication. Meanwhile, low and moderate self efficacy students have low mathematical communication skills. The use of Whatsapp media is not able to support students mathematical communication skill and self efficacy. The tachers need to design learning media to help students improve their mathematical communication skills and self efiicacy.